Dynamic mechanical behavior magnetorheological nanocomposites containing CNTs: a review - Ismail, R. (American Institute of Physics Inc., 2016)
Carbon nanotubes (CNTs) based polymer composites have variety of engineering applications due to their excellent mechanical, electrical, chemical, magnetic, etc. properties. This paper is an attempt to present a coherent yet concise review of as many of these publications as possible on the mechanical aspect of the Magnetorheological Elastomer (MRE) composites with the addition of multi-walled carbon nanotubes (CNTs). The dynamic mechanical response of the MR nanocomposites to applied magnetic fields has been investigated through dynamic mechanical analysis. It is found that a small amount of carbon nanotubes can effectively improve the mechanical performance of conventional MR elastomers. In summary, multi-walled carbon nanotubes reinforced magnetorheological composite has been developed to take advantage of both the smart MR technology and outstanding properties of carbon nanotubes. Furthermore review is also carried out on the capability of carbon nanotubes to impart the stiffness and damping performance encountered with the properties of CNT based Natural Rubber.